TOYA CAMPUHAN: AIR DAN PERADABAN MANUSIA DALAM PENCIPTAAN SENI LUKIS - Setem, I Wayan; Kondra, I Wayan; Gede Putra Jaya, I Made (Institut Seni Indoensia Surakarta, 2022)
TThe purpose of this research and art creation is to create and present artworks with “Toya Campuhan: Water and Human Civilization” as the source of inspiration. World civilization, especially in ancient Bali, has emerged and developed around water as its source of life. Water sources, such as river confluences, act as a pulse, supporting the joints that contribute significantly to various parts of physical and spiritual life. Due to this, water must be conserved, so that they always provide benefits for the journey of human life far into the future. However, the current condition of rivers in Bali is really worrying, as various pollutants pollute them. Slowly but surely, the water condition will worsen if we continue to let it be. This evokes my empathy, emotion, and hope about a healthy river confluence as a mission that I wanted to convey through the creation of this painting. This creation model becomes a cultural expression as a medium for increasing public appreciation to raise the spirit of ecological resilience over the problem of water pollution. This creation is based on research, where the method consists of two parts, namely the research method and the creation method. The research method uses an anthropological approach, especially related to ethnography. Meanwhile, the creation method passes through three stages: exploration, improvisation, and the embodiment of the work, which is preceded by a study of similar works of art and literature review.